The Structure Of Synthetic Parallelism In Arabic Poems: Al-Barudi's As A Model/ بنية التوازي التركيبي في الشعر العربي: البارودي نموذجا - Mohammed Hafees Mohammed Shareef; Rahmah Binti Ahmad H. Osman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Rhythm on both the external and internal levels is one of the most critical issues in Arabic poetic criticism. Analysis based on discovering rhythmic features is a crucial component in teaching poetic texts. The phenomenon of parallelism in all its forms has taken a prominent place in literary studies, owing to its impact on the internal rhythmic structure and its role in enriching the semantic structure of the Arabic poem. Against this backdrop, this study focuses on Bārūdī’s nationalistic poems to trace synthetic parallelism and the phenomena of Tarṣīʿ and Taqsīm, which have the feature of grammatical structure repetition, aiming to discover the rhythmic and semantic aspects. This study used the analytical method to trace Bārūdī's nationalistic poems in his Dīwān and the artistic approach to present and analyze the levels and patterns of previous literary devices recorded in his poems. The study found that synthetic parallelism is entirely and sometimes partially represented on two levels: vertical and horizontal, with the first being more common in Bārūdī’s poems. Similarly, the poet's desire to employ the most synthetic parallel between the two sequences emerged, while parallel morphological runs on most of their units. As for the significance produced by the similar structure, the importance of completion and contrast was employed in most parallelism models, and the significance of the affirmations represented in some of them. Likewise, the poet's artistic creativity was also evident in the composition of the phenomena of Tarṣīʿ and Taqsīm when their stops coincided with the (Tafʿīlah) measuring units' stops.